Neon aliens ate my homework : and other poems - Cannon, Nick, 1980- (Scholastic, Inc., 2015)
"With humor and heart, Nick Cannon--entertainer extraordinaire--has created a truly modern poetry collection. Join Cannon as he rhymes his way through a world filled with fantastical robots and dinosaurs, mean lunch ladies, terrifying babysitters, and a vegetarian who's had one too many bowls of beans. Also included are tributes to his family members, several children he's met on his travels, poet Shel Silverstein, and hip-hop icons."-Back cover.